Genomics of Maize Resistance to Fusarium Ear Rot and Fumonisin Contamination - Santiago, Rogelio (Toxins (Basel), 2020)
Food contamination with mycotoxins is a worldwide concern, because these toxins produced by several fungal species have detrimental effects on animal and/or human health. In maize, fumonisins are among the toxins with the highest threatening potential because they are mainly produced by Fusarium verticillioides, which is distributed worldwide. Plant breeding has emerged as an effective and environmentally safe method to reduce fumonisin levels in maize kernels, but although phenotypic selection has proved effective for improving resistance to fumonisin contamination, further resources should be mobilized to meet farmers’ needs. Selection based on molecular markers linked to quantitative trait loci (QTL) for resistance to fumonisin contamination or/and genotype values obtained using prediction models with markers distributed across the whole genome could speed up breeding progress. Therefore, in the current paper, previously identified genomic regions, genes, and/or pathways implicated in resistance to fumonisin accumulation will be reviewed. Studies done until now have provide many markers to be used by breeders, but to get further insight on plant mechanisms to defend against fungal infection and to limit fumonisin contamination, the genes behind those QTLs should be identified.